Estimating the economic effects of deregulation: Evidence from the Turkish airline industry - Tamer Çetin; Kadir Y. Eryiğit (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
This paper mainly studies the effect of deregulation on prices and quantity. For this aim, we employ cointegration methodology with structural breaks to empirically investigate the simultaneous relationship between deregulation, ticket prices, and the number of passengers in the Turkish airline industry. The findings confirm that deregulation increases quantity and decreases prices through accessibility to air transport service and actual competition, respectively. Also, structural breaks suggest that deregulation of prices and entry into the market has remarkable effect on the change in ticket prices and the number of passengers.
Keywords: L43; L93; C22; 330; Deregulation; Airlines; Cointegration; Structural Breaks